Design, synthesis, and discovery of 5-((1, 3-diphenyl-1H-pyrazol-4-yl)methylene)pyrimidine-2, 4, 6(1H, 3H, 5H)-triones and related derivatives as novel inhibitors of mPGES-1. Issue 5 (1st March 2018) - Ding, Kai; Zhou, Ziyuan; Zhou, Shuo; Yuan, Yaxia; Kim, Kyungbo; Zhang, Ting; Zheng, Xirong; Zheng, Fang; Zhan, Chang-Guo
Graphical abstract: Rational molecular design, followed by synthesis and in vitro activity assays for evaluating both the potency and selectivity, has led to the discovery of a set of novel, potent and selective mPGES-1 inhibitors. Abstract: Human mPGES-1 has emerged as a promising target in exploring a next generation of anti-inflammatory drugs, as selective mPGES-1 inhibitors are expected to discriminatively suppress the production of induced PGE2 without blocking the normal biosynthesis of other prostanoids including homeostatic PGE2 . Therefore, this therapeutic approach is believed to reduce the adverse effects associated with the application of traditional non-steroidal anti-inflammatory drugs (tNSAIDs) and selective COX-2 inhibitors (coxibs). Identified from structure-based virtue screening, the compound with ( Z )-5-benzylidene-2-iminothiazolidin-4-one scaffold was used as lead in rational design of novel inhibitors. Besides, we further designed, synthesized, and evaluated 5-((1, 3-diphenyl-1 H -pyrazol-4-yl)methylene)pyrimidine-2, 4, 6(1 H, 3 H, 5 H )-triones and structurally related derivatives for their in vitro inhibitory activities. According to in vitro activity assays, a number of these compounds were capable of inhibiting human mPGES-1, with the desirable selectivity for mPGES-1 over COX isozymes.